2013
DOI: 10.1002/cctc.201200730
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopalladated Arylimine Self‐Assembly Films for Suzuki Reaction

Abstract: A series of cyclopalladated arylimine self‐assembly films were prepared through chemical grafting to substrates and used to catalyze a Suzuki coupling reaction. Atomic force microscopy, water contact angle analysis, cyclic voltammetry, scanning electron microscopy, attenuated total‐reflectance infrared, and X‐ray photoelectron spectroscopy were used to analyze the morphology and composition of the heterogeneous catalysts. The results show that these cyclopalladated arylimine self‐assembly films immobilized on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Thus, an interaction exists between the reactants and supported catalyst films, which is consistent with previous studies. 19,41 These results indicated that is a heterogeneous catalyst catalyses the coupling reaction, which proceeded via a surface catalysis process.…”
Section: Investigation Of Catalytic Mechanismmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, an interaction exists between the reactants and supported catalyst films, which is consistent with previous studies. 19,41 These results indicated that is a heterogeneous catalyst catalyses the coupling reaction, which proceeded via a surface catalysis process.…”
Section: Investigation Of Catalytic Mechanismmentioning
confidence: 88%
“…18 The catalytic behaviour of a series of self-assembled Pd-arylimine complexes supported on silica in Suzuki coupling reactions has also been reported. 19 These synthesised catalysts show relatively high activity and stability in the long-term. However, a thorough study on the catalytic reaction mechanism has not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…25,[295][296][297] Recently, a cost profit of about 30%, providing that lignin is converted to value-added chemicals like phenolic monomers and oligomers, was showed. 298 In order to produce fuels from lignin, the phenolic monomers can be converted to alkanes (mono-and bicycloalkanes) or aromatics over bifunctional metal-loaded zeolites, like Pt on H-Y, H-beta or H-ZSM-5, [299][300][301] Pd/H-beta, 302 Ni/H-ZSM-5 [303][304][305][306] and Ru/H-ZSM-5, 307 or over a combination of a redox catalyst and a zeolite, like Pd/C and H-ZSM-5 308 or La/H-beta. 309 These transformations involve a series of reactions like hydrolysis, View Article Online dehydration, hydrogenation, cracking, alkylation and dealkylation.…”
Section: Multifunctional Catalysis With Sugar(-derived) Compoundsmentioning
confidence: 99%
“…We initially examined the influence of the nature of the base for the arylation of 5‐propyldibenzo[ b , f ]azepine, based on conditions that we had previously employed for the direct arylation of (hetero)aromatics . The use of 2 mol% PdCl(C 3 H 5 )(dppb) as catalyst [dppb: 1,4‐bis(diphenylphosphino)butane], KOAc as base in DMA with 1.2 equiv.…”
Section: Resultsmentioning
confidence: 99%